Growing Stevia plants Grow And Maintain Your Stevia Plants - Mitya Nitz (Everything Homemade, 2022)
Purpose of the book: To provide a practical, step-by-step guide for growing Stevia rebaudiana, a natural, zero-calorie sweet plant used as a sugar substitute. The book is aimed at gardeners and small-scale growers who want to cultivate stevia at home or on a small farm.